1997
DOI: 10.1016/s1350-4177(96)00015-6
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonically enhanced corrosion of 304L stainless steel II: The effect of frequency, acoustic power and horn to specimen distance

Abstract: The effects of frequency in the range 20 to 60 kHz, acoustic power and horn to specimen distance on the corrosion of 304L stainless steel in an ultrasonic field were investigated. At 40 and 60 kHz, the corrosion rate increased to a maximum and thereafter decreased with increasing transmitted power. At 20 kHz, the corrosion rate increased continuously with increasing power over the range investigated. At 18 W transmitted power, the corrosion rate increased continuously with frequency. However, at 40 W transmitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(27 citation statements)
references
References 20 publications
2
25
0
Order By: Relevance
“…Such an effect has been already observed by Whillock et al during the study of ultrasound-induced modifi cation of stainless steel. [ 45 ] They attributed the presence of this maximum to a peak in the cavitation intensity, which is supposed to increase with applied acoustic intensity as long as the collapse time allows the cavity to grow. In another way, an increase of the applied acoustic intensity could also enhance the number of acoustic bubbles between the horn and the sample.…”
Section: Ultrasonic Modifi Cation Of Oxide Materialsmentioning
confidence: 99%
“…Such an effect has been already observed by Whillock et al during the study of ultrasound-induced modifi cation of stainless steel. [ 45 ] They attributed the presence of this maximum to a peak in the cavitation intensity, which is supposed to increase with applied acoustic intensity as long as the collapse time allows the cavity to grow. In another way, an increase of the applied acoustic intensity could also enhance the number of acoustic bubbles between the horn and the sample.…”
Section: Ultrasonic Modifi Cation Of Oxide Materialsmentioning
confidence: 99%
“…The known cleaning effect of ultrasound due to the formation of liquid micro jets and shock waves generated by cavitation bubbles collapse can assist the initiated corrosion of electrodes at higher currents. Moreover, it was reported that ultrasound can both promote and suppress the corrosion of metals [21,22] . For that reason, the careful optimization of related parameters should be done for both EC, US and US-EC processes.…”
Section: High-performance Liquid Chromatographymentioning
confidence: 99%
“…On the other hand, a strong effect of hydrostatic pressure on cavitation was found, e.g. optimum pressure of 4.5 atm for a maximum aluminum foil erosion rate [13] or 4 bar for 304L stainless steel corrosion rate [14]. Hydrostatic pressure retards both cavity nucleation (reduction of the total number of cavities) and cavity growth (decrease in the sizes of cavities).…”
Section: Effect Of Pressure On Sonication Efficacymentioning
confidence: 99%